2007
DOI: 10.1111/j.1551-2916.2007.02031.x
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Dependence of the Conductivity of Pure and Tin‐Doped Indium Oxide on Oxygen Partial Pressure and Formation of an Intrinsic Defect Cluster

Abstract: The dependence of the electrical conductivity of pure (99.999%) and tin‐doped indium oxide (In2O3) ceramics on oxygen partial pressure was investigated at 800° and 850°C. The doping amount of tin was 100–1000 ppm, which is within the solubility limit at the temperatures measured. The conductivity of doped ceramics was independent of , and the carrier concentration was almost the same as the estimated value from the tin content. The conductivity of the pure In2O3 ceramic was proportional to. By consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…At about T = 600 K, the charge state V + O becomes populated as well as V 2+ O , which leads to a greater increase in n 0 with T . That increase then slows down at higher T , where E F and T are high enough that a significant concentration of V [32,62,63,191]. Of course, we have not considered other intrinsic defects, such as oxygen interstitials or cation vacancies, which may be present and act as electron killers, resulting in a lower n 0 .…”
Section: Charge Carrier and Defect Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…At about T = 600 K, the charge state V + O becomes populated as well as V 2+ O , which leads to a greater increase in n 0 with T . That increase then slows down at higher T , where E F and T are high enough that a significant concentration of V [32,62,63,191]. Of course, we have not considered other intrinsic defects, such as oxygen interstitials or cation vacancies, which may be present and act as electron killers, resulting in a lower n 0 .…”
Section: Charge Carrier and Defect Concentrationsmentioning
confidence: 99%
“…Varying P O 2 will change the concentrations of oxygen vacancies, which may act as donors, and interstitials, which may compensate n-type carriers, in a manner that depends on the defect chemistry of the system. It has been observed that, in undoped In 2 O 3 samples, the conductivity increases significantly as P O 2 is reduced [62]. Concurrently, the mobility decreases [21,63], which suggests that it is an increase in vacancy donor concentration, rather than a decrease of the concentration of compensating interstitials, that effects this increase in conductivity.…”
Section: Introductionmentioning
confidence: 98%
“…A special condition for realization of n-p transition in ITO film was found by authors of Ref. [27] at high temperature T>950 0 C. Minimum concentration of free electrons in polycrystalline samples prepared by using very pure components is not less than 10 17 cm -3 [4]. Doping of indium oxide by Sn can increase the density of free electrons up to 10 21 cm -3 .…”
Section: Introductionmentioning
confidence: 96%
“…Here we have accounted for the fact that, after doping with Sr, the density of electrons in In 2 O 3 was reduced by about 6 orders of the magnitude which can be inferred from the correspondent increase in resistance. Keeping in mind the concentration of free electrons of 10 17 cm -3 in undoped In 2 O 3 [4] and the above evaluated density of oxygen vacancies of about 10 19 cm -3 in oxygen deficient In 2 O 3 :(SrO) x , we assume that, in the latter compound, the major contribution in the number of electrons is due to oxygen vacancies as donors.…”
Section: Nonlinear Drift-diffusion Model Of Conductivitymentioning
confidence: 99%
See 1 more Smart Citation